Anti-glycan antibodies halt axon regeneration in a model of Guillain Barrè Syndrome axonal neuropathy by inducing microtubule disorganization via RhoA-ROCK-dependent inactivation of CRMP-2 - Rozés Salvador, María Victoria (2016)
Several reports have linked the presence of high titers of anti-Gg Abs with delayed recovery/poor prognosis in GBS. In most cases, failure to recover is associated with halted/deficient axon regeneration. Previous work identified that monoclonal and patient-derived anti-Gg Abs can act as inhibitory factors in an animal model of axon regeneration. Further studies using primary dorsal root ganglion neuron (DRGn) cultures demonstrated that anti-Gg Abs can inhibit neurite outgrowth by targeting gangliosides via activation of the small GTPase RhoA and its associated kinase (ROCK), a signaling pathway common to other established inhibitors of axon regeneration. We aimed to study the molecular basis of the inhibitory effect of anti-Gg abs on neurite outgrowth by dissecting the molecular dynamics of growth cones (GC) cytoskeleton in relation to the spatial-temporal analysis of RhoA activity. We now report that axon growth inhibition in DRGn induced by a well characterized mAb targeting gangliosides GD1a/GT1b involves: i) an early RhoA/ROCK-independent collapse of lamellipodia; ii) a RhoA/ROCK-dependent shrinking of filopodia; and iii) alteration of GC microtubule organization/and presumably dynamics via RhoA/ROCK-dependent phosphorylation of CRMP-2 at threonine 555. Our results also show that mAb 1B7 inhibits peripheral axon regeneration in an animal model via phosphorylation/inactivation of CRMP-2 at threonine 555. Overall, our data may help to explain the molecular mechanisms underlying impaired nerve repair in GBS. Future work should define RhoA-independent pathway/s and effectors regulating actin cytoskeleton, thus providing an opportunity for the design of a successful therapy to guarantee an efficient target reinnervation.